Digitalization Capabilities on Route to Attaining Sustainable Auditing Ecosystem with Role of Accountants’ Digital Intelligence - Huy, Pham Quang; Phuc, Vu Kien (Journal of Environmental Accounting and Management, 2026)
This manuscript sets its sight on catering to a consistent picture of how Digitalization Capabilities (DC) demonstrates an impact on Sustainable Auditing Ecosystem (SAE) in public sector organizations (PSOs) of developing countries with a concentration on Vietnam, and gives insights regarding to impacts of Accountants’ Digital Intelligence (ADI) in the interconnection between DC and SAE. The structural equation modelling was employed to mathematically analyze the survey data captured from self-administered questionnaire circulated to a convenient and snowball sample of 512 respondents. The acquired outcomes provided statistical evidences to undergird all the proposed hypotheses in the conceptual model. Beyond acting as a fruitful springboard for follow-up studies, the value of more fine-grained insights in this work could guide the practitioners to sense and seize the value of digitalization through formulating strategies and devising interventions pertaining to digitalization issues in PSOs. At the policy degree, the current research also generated a systemic model to formulate and cultivate measures addressing challenges in term of digitalization which thus enabled the design of policies and initiatives for a more inclusive and sustainable collaboration.